Psychological Trauma - Starcevic, Ana; Starcevic, Ana (IntechOpen, 2019)
Trauma presents as a negative experience or situation of an individual in which coping mechanisms do not always work perfectly. This leads to the appearance of disturbing behavior, thinking, or developing disorders in the area of mental illnesses. Psychological trauma is related to chronic and repetitive experiences and the term and situation that refer to it must be consider objectively because it is up to each survivor to determine if it is traumatic. Future studies in the area of psychological trauma need to be conducted with the aim of defining anatomical correlates of stress and its underlying pathophysiological mechanisms.
English
Keywords: Psychology; Psychology